Cardiac Biomarkers and Cardiovascular Outcome in Children with Chronic Kidney Disease (Iranian Journal of Kidney Diseases, 2019)
Introduction. Myocardial dysfunction is a leading cause of mortality in chronic kidney disease (CKD) children specially those on regular hemodialysis. Cardiac biomarkers play a key role for early detection of myocardial injury. We aim to clarify the prognostic role of circulating cardiac biomarkers, heart type fatty acid binding protein (H-FABP) and pregnancy associated plasma protein-A (PAPP-A) in CKD children on regular hemodialysis. Material and Methods. This is a prospective case control study over 2 years duration. Initial assessment included 20 CKD children on regular hemodialysis and 20 age- and sex- matched healthy children as a control group. Serum level of H-FABP and PAPP-A were measured and correlated to conventional echocardiographic findings and cardiovascular outcome in CKD children. Results. 60% of CKD children developed cardiovascular comorbidities. H-FABP and PAPP-A levels were significantly elevated especially in those with worse cardiovascular outcome. H-FABP and PASP-A levels were positively correlated with LVM index. At cut off point > 17.65 pg/mL, H-FABP has 91% sensitivity and 87.5% specificity for prediction of cardiac morbidity. Elevated H-FABP (OR = 33; CI 95%: 2.455 - 443.591), LVM indexed to body surface area (OR = 21; CI 95%: 1.777 - 248.103), LVM indexed to lean body mass (OR = 15; CI 95%: 1.652 -136.172), elevated PAPP-A (OR = 9.8; CI 95%: 0.898 - 106.845) and Hypertension (OR = 8.333; CI 95%: 1.034 - 67.142) are the main risk factors for cardiac morbidities in CKD children. Conclusions. Elevated H-FABP and PAPP-A are valuable prognostic markers for cardiovascular outcome in CKD children on regular hemodialysis.